KEBIJAKAN PEMERINTAH KABUPATEN BENGKALIS DALAM PENGEMBANGAN KAWASAN PUSAT PENDIDIKAN TAHUN 2010-2015 - Prayogi, Esra Riko; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
On the Medium Term Development Plan 2010-2015 Bengkalis regency, set Grand Strategy development of four areas, one of which is the development of regional education centers. In its development until the term of office of Regent of Bengkalis period 2010-2015, a number of programs and activities in realizing Bengkalis as a center of education can not be realized with the maximum. The purpose of the study is to examine the implementation of regional development policy education center and the factors that affect the implementation of the policy of regional development center for education research method is qualitative descriptive research data collection is by interview and documentation. The theory used in this research is the policy and implementation of policies according to Van Meter and Van Horn.From the results of the field studies showed that some programs and activities in the development of the central area of education is not achieved by maksmimal not even be possible. It can be seen from the projects was State Health Polytechnic and State University who is an excellent program, it was not implemented because of the limited authority, the authority of the organization of Higher Education where it is still in the center. Further Development of High School Boarding School can not be realized with the maximum due to budget constraints and not professional tenders. The factors that affect the implementation of regional development policy education center in Bengkalis based theory of policy implementation, namely: basic measures and policy objectives, policy resources, communication between the organization and implementation of activities, the characteristics of the implementing agencies, conditions- economic, social and political, executive attitudes. In this study the authors concluded that the Education Department has tried to realize the regional development policy education center although in the end there are some problems that cause programs and activities can not be achieved with the maximum. Bengkalis District Government should still continue the programs and activities in the development of the central area of education and must evaluate the programs that can not be done.Keywords: Policy, Development Education Center Region